If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7u + 46 = 9(u + -2) Reorder the terms: 46 + -7u = 9(u + -2) Reorder the terms: 46 + -7u = 9(-2 + u) 46 + -7u = (-2 * 9 + u * 9) 46 + -7u = (-18 + 9u) Solving 46 + -7u = -18 + 9u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-9u' to each side of the equation. 46 + -7u + -9u = -18 + 9u + -9u Combine like terms: -7u + -9u = -16u 46 + -16u = -18 + 9u + -9u Combine like terms: 9u + -9u = 0 46 + -16u = -18 + 0 46 + -16u = -18 Add '-46' to each side of the equation. 46 + -46 + -16u = -18 + -46 Combine like terms: 46 + -46 = 0 0 + -16u = -18 + -46 -16u = -18 + -46 Combine like terms: -18 + -46 = -64 -16u = -64 Divide each side by '-16'. u = 4 Simplifying u = 4
| 4x^2+52x+146=0 | | -2(x-30)+4x=-x+1 | | 16x+29= | | -0.5x+1.97=-0.7x+2.57 | | -2(x-30)+4x=-x+1 | | 6x+3y=4725 | | 10+3x=17x+3 | | 5x+23=82 | | 10+3x=17x+3 | | 16m^2=80 | | 5x+23=82 | | 16m^2=80 | | -1+5+x= | | 5x-15+8=14x+2 | | 2y^2-32=-32 | | 2(4x+y)= | | 4.5x-16=2.6x+3 | | 3q+9q=18 | | R^2+rst+5r+5st=0 | | -2x+7=-5x+6x+10 | | 16m^2=8m*10m | | 2(x-4)=x+4 | | 6=(-x-3) | | 2x^2-6x+32=0 | | A=a+(n-1)(d) | | -4+r= | | 14=10x+4 | | 2x-8y-6=0 | | 4d+18+9d= | | (2x-3)-(4x-5)=6y | | 7(x-4.5)=2.8 | | -4+r+20= |